An aggressive pyogenic granuloma masquerading as a vascular neoplasm - Shravya Jaganath Shetty; Kaveri Hallikeri; Venkatesh Anehosur; Anil Desai (Wolters Kluwer Medknow Publications, 2020)
Pyogenic granuloma (PG) is a benign lesion, with a female predilection, commonly associated with local irritation or trauma. We report an unusual, destructive case of PG, displaying excessive loss of blood and destruction of alveolar bone leading to the loss of maxillary anterior teeth in an 18-year-old female, compromising function and esthetics. The incisional and excisional biopsy specimen of this recurrent lesion obtained during a 5-year span was studied, which revealed an increase in vascularity and extensive proliferation of endothelial cells admixed with varying degree of inflammatory cell infiltrate. The clinical, radiographic, and histopathological diagnostic tools enabled to precisely diagnose the lesion as an aggressive variant of PG, distinguishing it from other vascular neoplasms. No recurrence has been noted during a 5-year follow-up. The clinicians should be aware of the aggressive and destructive clinical behavior of PG to avoid the inadvertent treatment of this reactive lesion.